2020
DOI: 10.3390/jcm9010154
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Administration of Dienogest for the Treatment of Pain and Intestinal Symptoms in Patients with Rectosigmoid Endometriosis

Abstract: Background: Rectosigmoid endometriosis is a severe form of deep endometriosis, which may be responsible for pain symptoms and a wide range of intestinal complains such as diarrhea, constipation, and abdominal cramping. The primary objective of this study was to evaluate the efficacy of long-term therapy with dienogest (DNG), a fourth-generation progestin, for ameliorating quality of life, pain, and intestinal symptoms of patients affected by rectosigmoid endometriosis. Methods: A retrospective analysis of a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 33 publications
(49 reference statements)
2
17
0
1
Order By: Relevance
“…In our examination 24% were having endometriosis. Then again Techatraisak K et al [7] (2019) all patients 864/864 100% patients had history of endometriosis. In the examination Caruso S. et al [8] (2018) most normal manifestation was constant pelvic torment in 100% (n=51) ladies, dysmenorrhea n=50 (78.4%) and Dyspareunia n=38 (74.5%).…”
Section: Discussionmentioning
confidence: 93%
“…In our examination 24% were having endometriosis. Then again Techatraisak K et al [7] (2019) all patients 864/864 100% patients had history of endometriosis. In the examination Caruso S. et al [8] (2018) most normal manifestation was constant pelvic torment in 100% (n=51) ladies, dysmenorrhea n=50 (78.4%) and Dyspareunia n=38 (74.5%).…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, Egekvist et al [29] observed that progression of nodule volume dimensions occurred without worsening of symptoms or healthrelated quality of life. Barra et al [33] also confirmed that the increase in endometriotic nodule volume during dienogest therapy was not always associated with worsening of clinical symptoms.…”
Section: Rationale For Hormonal Treatment Of Bowel Endometriosismentioning
confidence: 87%
“…Barra et al [33] [32] reported persistence of pain symptoms in the vast majority of women in whom the nodule regressed or remained stable. On the other hand, Egekvist et al [29] observed that progression of nodule volume dimensions occurred without worsening of symptoms or healthrelated quality of life.…”
Section: Rationale For Hormonal Treatment Of Bowel Endometriosismentioning
confidence: 99%
See 2 more Smart Citations